2008
DOI: 10.1530/eje-08-0496
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac manifestations of GH deficiency after treatment for acromegaly: a comparison to patients with biochemical remission and controls

Abstract: Objective: Both GH excess and GH deficiency (GHD) lead to specific cardiac pathology. The aim of this study was to evaluate cardiac morphology and function in patients with GHD after treatment for acromegaly. Design: Cross-sectional study. Patients and methods: Cardiac parameters were studied by conventional two-dimensional echocardiography and tissue Doppler imaging in 53 patients with acromegaly (16 patients with GHD, 20 patients with biochemical remission, and 17 patients with active disease). Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Also, the acromegaly-related cardiac abnormalities could worsen after the development of GHD [101]. However, clinical studies do not fully confirm these theoretical hypotheses, as they found a BMI slightly increased [102][103][104] or, even, similar [105][106][107][108] in acroGHD compared to GHD and acromegalic populations. At the same time, while one work reported that acroGHD patients were more hypertensive, dyslipidemic, and diabetic than GHD subjects [109], other Authors pointed out a comparable prevalence of glucose abnormalities and dyslipidemia, as well as a similar amount of body fat and lean mass between acroGHD and refcerebrovascular [5, [82][83][84][85][86][87].…”
Section: B Ghd After Treatment Of Acromegaly (Acroghd)mentioning
confidence: 99%
“…Also, the acromegaly-related cardiac abnormalities could worsen after the development of GHD [101]. However, clinical studies do not fully confirm these theoretical hypotheses, as they found a BMI slightly increased [102][103][104] or, even, similar [105][106][107][108] in acroGHD compared to GHD and acromegalic populations. At the same time, while one work reported that acroGHD patients were more hypertensive, dyslipidemic, and diabetic than GHD subjects [109], other Authors pointed out a comparable prevalence of glucose abnormalities and dyslipidemia, as well as a similar amount of body fat and lean mass between acroGHD and refcerebrovascular [5, [82][83][84][85][86][87].…”
Section: B Ghd After Treatment Of Acromegaly (Acroghd)mentioning
confidence: 99%
“…Additionally, growth hormone deficiency (GHD) that may arise after the treatment may have a deleterious effect on diastolic function. 35) In our study, GHD was not evaluated. Conclusion: The present study confirmed the increased prevalence of LVDD in acromegaly using the new echocardiographic criteria.…”
Section: Discussionmentioning
confidence: 90%
“…In three studies, patients who were GH sufficient after treatment for acromegaly or active acromegaly were used as controls. These studies demonstrated that GHD after treatment for acromegaly is associated with a more impaired metabolic profile (15,16,27). Studies using GHD of other etiologies or after treatment for a NFPA as comparator demonstrated no differences in clinical presentation (6,17,26).…”
Section: European Journal Of Endocrinologymentioning
confidence: 93%
“…To date, ten studies (Table 4) investigated the characteristics of GHD and/or the effect of GH treatment on cardiovascular outcome measures in GHD patients after treatment for acromegaly (6,15,16,17,18,19,20,26,27,28). In three studies, patients who were GH sufficient after treatment for acromegaly or active acromegaly were used as controls.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation